The Impact of Vitamin D Deficiency on Retinopathy and Hearing Loss among Type 2 Diabetic Patients. (9th July 2018) - Bener, Abdulbari; Eliaçık, Mustafa; Cincik, Hakan; Öztürk, Mustafa; DeFronzo, Ralph A.; Abdul-Ghani, Muhammad
Abstract : Aim . The current study was aiming to investigate the relation between vitamin D, retinopathy, and hearing loss among type 2 diabetes mellitus (T2DM) patients. Methods . Cross-sectional study carried on 638 subjects aged between 20 and 60 years who visited the Endocrinology, Ophthalmology, and ENT Outpatient Clinics of the Medipol Hospital during the period from March 2016 to May 2017. Two audiometers Grason Stadler GSI 61 and Interacoustics AC40 Clinical audiometer were used to evaluate the hearing loss. Risk factors for diabetic retinopathy were evaluated, including age, sex, diabetes duration, glycated hemoglobin (HbA1c), hypertension, and lipid profiles. Results . The mean age (± SD, in years) for retinopathy with hearing loss versus normal subjects was 47.7 ±10.2 versus 48.5±9.1. The associated risk factors were significantly higher in T2DM with hearing loss, hypertension (32.6% versus 15.7%), tinnitus (40.0% versus 18.0%), vertigo (59.7% versus 26.8%), and headache (54.9% versus 45.3%), than in normal hearing diabetes. There were statistically significant differences between hearing impairment versus normal hearing for vitamin D [19.40±9.71 ng/ml versus 22.67±9.28 ng/ml; p<0.001], calcium, magnesium, phosphorous, cholesterol, HDL-C, LDL-C, albumin, systolic blood pressure [131.70±9.25 Hg versus 127.73±11.98 Hg], diastolic blood pressure [82.20±8.60 mm Hg versus 79.80±8.20 mm Hg], and microalbuminuria. Multivariate logistic regression analysis revealed that variables such as vertigo, duration of DM, mobile/I pad phone, vitamin D deficiency, sleeping disturbance, headache, frequently TV watching, tinnitus, cigarette smokers, and hypertension were considered at higher risk as a predictors of retinopathy with hearing loss among diabetic patients. Conclusion . Vitamin D deficiency is considered as a risk factor for diabetic retinopathy and hearing loss among diabetic patients. Meanwhile, hyperglycemia could be considered as a modifiable risk factor for diabetic retinopathy; tight glycemic control may be the most effective and important therapy for improving quality of life and substantially reducing the incidence of retinopathy and in T2DM patients.